Does Transfer Pricing, Sales Growth, Foreign Ownership, Asset Intensity Affect Tax Avoidance in Energy Companies in Indonesia? - Rio dhani Laksana; Intan Shaferi; İlkay Aydoğmuş (Syntax Corporation Indonesia, 2023)
Tax avoidance measures are carried out because of different interests on the part of the government and the companies, where the government needs to increase state revenues through large tax revenues while the companies want taxes to be as minimal as possible because taxes are a burden that reduces profits. The research aims to examine transfer pricing, sales growth, asset intensity and Foreign Ownership affected on tax avoidance in energy companies in Indonesia. A sample of companies in the energy sector that were listed on the Indonesia Stock Exchange (IDX) between 2020 and 2022 was selected. Descriptive statistical tests, conventional assumptions, multiple regression analysis, and hypothesis testing. According to the test, the findings of this study show that transfer pricing and asset intensity has positive impacts impacts tax avoidance. Sales Growth and Foreign ownership, have a negative impact on tax avoidance